2007
DOI: 10.1016/j.joen.2006.12.004
|View full text |Cite
|
Sign up to set email alerts
|

The Root and Root Canal Morphology of the Human Mandibular First Premolar: A Literature Review

Abstract: The purpose of this study was to undertake a comprehensive literature review of the root and root canal morphology of the mandibular first premolar. Published studies citing the anatomy and morphology of mandibular premolars report data for over 6,700 teeth. These studies were divided into anatomical studies reporting number of roots, number of canals, and apical morphology. Variations because of sex and ethnic background have also been reported, along with case reports of anomalies. Approximately 98% of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

29
149
3
31

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 182 publications
(212 citation statements)
references
References 58 publications
29
149
3
31
Order By: Relevance
“…of the numerous variations in root canal morphology usually associated with the presence of developmental root concavities (9,17,20). In the present study, the incidence of RG in mandibular first premolars (14%) was similar to that reported by Velmurugan and Sandhya (21), but lower in comparison to the Chinese population (24% to 27.8%) (13,18).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…of the numerous variations in root canal morphology usually associated with the presence of developmental root concavities (9,17,20). In the present study, the incidence of RG in mandibular first premolars (14%) was similar to that reported by Velmurugan and Sandhya (21), but lower in comparison to the Chinese population (24% to 27.8%) (13,18).…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the incidence of RG in mandibular first premolars (14%) was similar to that reported by Velmurugan and Sandhya (21), but lower in comparison to the Chinese population (24% to 27.8%) (13,18). This discrepancy has been mostly attributed to racial factors, but also to diversities in sample size, study design, and evaluation method (9). While a common standard has been used for identification of RG, herein, premolar teeth were selected based on the ASUDAS (12), a common standardized tool used in anthropology that allows to set more precisely a threshold between a slight root depression and a typical groove, overcoming the lack of accuracy in sample selection that may have compromised some previous studies.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations